Discrimination of Hypotrigona species (Apidae : Meliponinae) in Kenya using nest architecture, cephalic secretions and molecular tools - Pirk, Christian Walter Werner (University of Pretoria, 2026)
Thesis (PhD (Entomology))--University of Pretoria, 2019.